(untitled) (Bulletin KNOB, 1992)
From approximately 1910 to 1947 the architect ir. G.C. Bremer made an important contribution to Dutch architecture. For the greater part of that period, from 1924 to 1946, he was Government Architect. Bremer’s oeuvre is quite divergent in character; it does not represent any clearly defined style or specific trend. The buildings executed by him comprise traditionalist elements as well as elements of ’New Realism’, depending on what views the commission in question required of him. Indeed, Bremer did not play a part in the architecture debate between the representatives of ’New Building’ and the traditionalists. This may well be one of the reasons why his work no longer attracts much attention from architectural historians. From 1910 onwards Bremer had an architects’ firm in Arnhem, together with the architect A.R. Freem. From 1914 to 1915 he was temporarily appointed town architect of Arnhem. In 1916 he took up office with ‘Landsgebouwen’, the predecessor of the ‘Rijksgebouwendienst’ (i.e. a service of the Ministry of Housing and Construction). On January 1st 1924 Bremer was appointed Government Architect with the Rijksgebouwendienst, which had then just been established, where he was responsible for all new construction. Until his retirement on January 1st 1946 he remained in office there. Bremer had a preference for medieval architecture, both its form language and the underlying starting-points appealed to him. His view was that in medieval architecture there had still been room for the craftsman, and that the latter could be put on a par with the architect. Clear references, notably to Romanesque architecture, can also be traced in his buildings, although these often concern idiosyncratic interpretations, such as the frequent use of arches (in windows and portals), the use of natural stone as a building material and the intensive cooperation with artists, who made decorations for the buildings in the form of statues, murals and stained-glass windows. Some of Bremer’s buildings show that his admiration for certain architects resulted in imitation. This is particularly evident with reference to Berlage (not only in his initial period, but continuing up to his last works) and also with reference to Oud and Friedhoff. As the person having final responsibility, Bremer has left his mark on the buildings executed by the Rijksgebouwendienst in the period until 1947. This is visible in several buildings, not built in his name, but nevertheless showing a close affinity with his work, such as the building for the National Giro Bank and the building for the Patent Office plus Post Office on the Willem Witsenplein in The Hague. With the Landsgebouwen/Rijksgebouwendienst Bremer mainly executed buildings for the Post Office Board - including post offices, telephone exchanges and amplifier stations - but also tax-collection offices, government buildings and a court-house. He also provided designs for laboratories and for the Wilhelmina bridge in Maastricht. It is not easy to define any sort of line in Bremer’s oeuvre, to discover a constant or to recognize any order in his multiform designs. It is also difficult to place the various designs in a logical, chronological development. Neither does one design naturally evolve from another. Even within one and the same design he applied different styles. What appears to be characteristic of Bremer’s work is the fact that it is homogeneous and heterogeneous at the same time. His conception is homogeneous, his style heterogeneous; the designs of his buildings are to a great extent determined by their purpose and environment. A list of fifty works by ir. G.C. Bremer is included in this article.